JENIS-JENIS TUMBUHAN PALEM TEGAK DAN KAJIAN ETNOBOTANI DI DUSUN SALUKI DESA TUWA KECAMATAN GUMBASA KABUPATEN SIGI SULAWESI TENGAH - Achmad Ramli; Samsurizal M. Suleman; Ramadanil Ramadanil (Biology Department, Mathematics and natural science, Tadulako University, 2019)
The Research entitled “Diversity of erect palm species and its Etnobotanical study at Tuwa Village Saluki Hamlet Gumbasa district, Sigi regency” has been conducted from October to December 2016. The research aimed to study the diversity of Arecaceae and its usefulness by local people in the studied area. The metode of collecting data and sample conducted a survey include exploration in the field without ignoring the abiotic factors include temperature and humidity, well as tte questionnaire interviews with responden 10 people. The results showed that 9 species of Arecaceae with aspects of their use people in the tuwa village saluki hamlet. The data analysis of Arecaceae plants untilized by the community that is 4 aspect, which consists of medicine (2 species), food (4 species), crafts (1 species), and building materials (3 species).